Xiaochaihutang Inhibits the Activation of Hepatic Stellate Cell Line T6 Through the Nrf2 Pathway - Hu, Rui; Jia, Wei-yi; Xu, Shang-fu; Zhu, Zhi-wei; Xiao, Zhi; Yu, Shou-yang; Li, Jin (Frontiers in Pharmacology, 2019)
Xiaochaihutang (XCHT) is one of classic prescriptions in Treatise on Febrile Diseases in China which was reported to have the effect of anti-hepatic fibrosis in vivo. Activation of hepatic stellate cells (HSCs) is now well established as a central driver of fibrosis in liver injury. Nuclear factor erythroid 2-related factor 2 (Nrf2) is an important element for anti-oxidative damage which is one of the key factors responsible for occurrence. This study was to investigate the effect of XCHT compound serum on HSCs activation and focus on the Nrf2 pathway. Rats in treatment groups were given the appropriate doses of XCHT granules (5 g/kg) and Silybin (50 mg/kg) for 6 days, and the serum were obtained. The compound serum was used to intervene HSCs. The results found that XCHT compound serum significantly inhibited the proliferation of HSCT6 cells. The number of α-SMA positive stained cells in HSCT6 cells and the content of Collagen type I (collagen-I) in supernatant were significantly decreased indicating suppression of activated HSCs. Compared with the control group, the nuclear transcription of Nrf2 and the expressions of Nqo1, GCLC and GCLM were significantly increased in XCHT group. However, the effects of XCHT were inhibited in Nrf2-siRNA transfected HSCT6 cells. These studies demonstrated that XCHT could inhibit HSCT6 cell proliferation and activation. The mechanism might be related to up-regulation of the Nrf2 pathway against oxidative stress.